PATIENT SAFETY PERCEPTION AMONG MEDICAL AND NURSING STUDENTS: THE REVIEW - Jamil, Noorsalfizah (The journal of contemporary issues in business and government, 2021)
Patient safety has been broadly conceptualized as the prevention of unnecessary patient harm or potential harm. In order to meet the goal of harm prevention in a clinical setting, the patient safety is recommended as an important practice being implementing by the healthcare team in the clinical setting. It is because, the patient safety practice may emphasize on the reduction and mitigation of unsafe acts within the healthcare system, and then it is also known as the best practice that lead to the optimal health outcome of the patients. The patient safety issue had been recognized as the global problem where it is needs the global solutions. Safety is emphasized as the main concern in health system performance and quality management in the healthcare services. The improvement in patient safety and quality of the healthcare services had been identified as an important issue in the healthcare services worldwide.